O direito de propriedade e sua função social: uma discussão a partir da Teoria de John Rawls em oposição a John Locke e Robert Nozick - Pizetta, Andreia Schossler Loss (2009)
The present work approaches the matter of the Law of Property and its social function according to John Rawls theory of justice, having the intention to understand what the role of the property is to the author, the ways of property which are considered fair by him and, if it answers to the principles of justice and property which fitted with its social purpose. For such, it deals with, firstly, in chapter 1, the conteporary conception of law of property, which is inserted within a more humanitary, cooperative pespective of society and reciprocity, longing to a socialeconomical harmony and the effectiviness of certain human necesseties to improve the pespective of the citizens lives. Carrying on in this chapter, it is studied Locke s concept of private property to demonstrate the points where his theory disagree with John Rawls theory, thus it brings more individual view of property and it adopts a restricted conception of this right. Locke defends the unlimited accumulation of wealth, being the property turned, only, to the individual growth of the owner and to benefit the business, and then not existing a distributive and cooperative justice. Macpherson criticizes Locke s theory since it is extremely individualist. Chapter 2 aims to analyse the main ideas of Rawls theory of justice, seaching for the main and fundamental concepts so that chapter 3 is well-understood. Rawls supports the distributive justice and encourages the social cooperation. For this author, the basic liberties are inegotiable and the object of his theory is the basic structure of the society as an equitative system of social cooperation among free and iqual citizens. In order to reach this, the individuals make an agreement under the veil of ignorance to formulate the principles of justice which will run the institutions of a democratic constitutional fair society. Chapter 3 fights against the matter of the law of property for this author, a big suppoter of the distributive justice and of the social cooperation, which understands the law of property as basic good, because it helps to accomplish the expectations of the citizens lives, and it must also be capatible to the other rights and liberties which belong to a social system to provide a honored life. Rawls thought was a target for criticism by Robert Nozick, whom rescued Locke s theory of appropriation, not agreeing with the notion of distributive justice and of social cooperation, counteracting in several points to the Rawls theory of justice. However, according to the philosophers Álvaro de Vita, Will Kimlicka and Van Parijs, the defense of John Rawls theory was made, because they support the thought of this author, abova all objections shown by Nozick. Thus, the right of property must have a social mean to promote certain basic needs of the individuals, and this is clear in Rawls work so that he believes in social cooperation, in the effectiviness of human dignity, of self-respect, of self-steem and of their own citizenship, through a distributive justice.